Microwave Photonic Filter by Using Recirculating Frequency Shifter to Generate Optical Frequency Comb - Weiyu Dai; Weiying Rao; Haoran Wang; Hongyan Fu (IEEE Photonics Journal, 2021)
In this paper, a continuously tunable microwave photonic filter (MPF) with optical frequency comb (OFC) generated by recirculating frequency shifter (RFS) based on an inphase/quadrature (I/Q) modulator is proposed and experimentally demonstrated. A chirped fiber Bragg grating (CFBG) is inserted into the RFS loop to act as an optical bandpass filter. The central frequencies of two passbands of the MPF in 20 GHz range have been tuned linearly from 7.67 GHz to 9.04 GHz, and 15.34 GHz to 18.03 GHz, respectively by changing the frequency of the driving microwave signal onto the I/Q modulator from 20 GHz to 17 GHz. When the frequency of the driving microwave signal is decreased, OFC with smaller tone spacing is generated, and then the MPF's passbands move to higher frequency. So that, the proposed MPF's passbands with high frequencies can be achieved by applying driving microwave signal with low frequency to generate the OFC. By varying the bandwidth of the CFBG, the number of comb lines can be changed, which results in different bandwidth of the MPF's passband. Furthermore, in our experiment by carefully adjusting bias voltage of the Mach-Zenhder modulator, when the frequencies of driving microwave signal onto the I/Q modulator is 20 GHz and 18 GHz, one passband in the 20 GHz range can be suppressed at the frequency of 15.34 GHz, and 8.52 GHz, respectively.